PENGARUH KONDISI SOSIAL EKONOMI MASYARAKAT TERHADAP POLA PEMAKAIAN AIR DOMESTIK - Hermin Poedjiastoeti (Universitas Islam Sultan Agung, 2012)
Kalasan subdistrict is located in Yogyakarta Special Region, in which its development expands to the north as well as to the east. Kalasan subdistrict is one of the eastern areas ofYogyakartawhich is in the developing process of population, sosial, economics, and culture. These developments affect the domestic water utilization that is analyzed based on the type of job, education level, income level, and the type of water source.The objectives of this research are (1) to recognize the needs of domestic water in Kalasan subdistric in different sosial economic level; (2) to recognize the need of water on the peak hour and the daily maximum utilization; (3) to examine the effect of the water source type on the domestic water utilization for daily use.Methods used in this research include interview to gather data based on stratified proportional random sampling. The data analysis covered the descriptive analysis with cross tabulation and statistic analysis with Multiple Regression, and alsoChi Square. The data gathered are the water use by the member of family, the type of job, education level, income level, and the type of the water source.This research get the result that is: (1). Water utilization per capita in Kalasan Subdistrict have come up to like water utilization in small town specified by Dirjen Cipta Karya Departemen Pekerjaan Umum of equal to 130 litre/capita/day; (2). Education level in Kalasan Subdistrict have an effect on to domestic water utilization, this matter indicate that the excelsior mount the education, ever greater hence water utilizated, so that mount the high education tend to utilize the water more extravagant; (3). Income level do not have an effect on to domestic water utilization; (4). Domestic water utilization in Kalasan Subdistrict is not defined by certain type of job; (5). Water utilization on peak hour in the morning is 266,73 litre/day, while water utilization on daily maximum is 774,09 litre/day which be at the Sunday, peak hour factor in Kalasan Subdistrict is 1,30 and daily maximum factor is 1,26; (6). Domestic water utilization determined by certain water source type. Keywords : water utilization, peak hour, and maximum daily water utilization